ФОНЕТИЧЕСКАЯ ИНТЕРФЕРЕНЦИЯ И ЕЕ ПРИЧИНЫ - Алиева Б. Б. (World Science, 2018)
The article deals with the problem of interference arising in the process of teaching a foreign language. The types of interference due to distinguished the nature of the interaction of the native and foreign languages, the subjective and objective factors on which the depth and volume of interference depend, the wide and narrow interpretation of the term interference, the need to distinguish between interference phenomena and analogy are considered. Particular attention is paid to phonetic interference and pronouncing accent, the reasons for their occurrence and the appearance of two types of accent in the speaker's speech.Interference, being an integral part of the process of mastering a foreign language, manifests itself in different parts of the sound system, and attention is drawn to the subordination of these errors to certain regularities. The set of admitted errors is not accidental, but is programmed by the peculiarities of the native language, and the knowledge of this program allows to predict errors in the Russian language speech of foreign students.